2017
DOI: 10.1016/j.juro.2017.02.155
|View full text |Cite
|
Sign up to set email alerts
|

Mp04-17 Blood-Based Biomarkers as Predictors of Oncologic Outcomes for Non-Muscle-Invasive Urothelial Bladder Carcinoma

Abstract: This represents the largest study to date evaluating outcomes following RC in HD patients. RC is associated with significant morbidity and less than 20% of patients survive 5 years. Older patients, female patients, and those with a history of CHF or diabetes are at an increased risk of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These blood-based biomarkers were taken from 328 patients before TURBT. They found that CEA and CA 19-9 levels were significantly higher in patients who had a recurrence and/or progression compared to those who had no recurrence-CA125 did not differ between the two groups after a mean follow-up of 4.9 years [11]. The authors concluded that further larger future studies should consider including these biomarkers in a predictive model.…”
Section: Biomarkersmentioning
confidence: 96%
“…These blood-based biomarkers were taken from 328 patients before TURBT. They found that CEA and CA 19-9 levels were significantly higher in patients who had a recurrence and/or progression compared to those who had no recurrence-CA125 did not differ between the two groups after a mean follow-up of 4.9 years [11]. The authors concluded that further larger future studies should consider including these biomarkers in a predictive model.…”
Section: Biomarkersmentioning
confidence: 96%